Responsive Parenting and Nutritional Status Among Children with a History of Stunting : A Scoping Review - Rismanudin Rismanudin; Wiwiek Hidayati Jaya; Wahyuni Hafid (PT.Mantaya Idea Batara, 2025)
Introduction: Stunting remains a significant global public health challenge, affecting over 148 million children worldwide and resulting in long-term impairments in cognitive development, immunity, and future productivity. Although nutrition-specific interventions have been extensively implemented, the influence of parenting behaviors on recovery among children with a history of stunting has not been comprehensively synthesized. This scoping review examines how responsive parenting, grounded in evidence-based practice, affects nutritional outcomes and developmental recovery in children with a history of stunting. Methods: The review adhered to PRISMA-ScR guidelines and employed the Population–Concept–Context (PCC) framework. A systematic search was performed across PubMed, Scopus, ScienceDirect, and Google Scholar for studies published between 2020 and 2025. Eligible articles, written in English or Indonesian, investigated responsive parenting, caregiving behaviors, or evidence-based parenting interventions related to nutritional outcomes. Twenty-seven studies met the inclusion criteria and were analyzed using narrative and thematic synthesis. Result: The results demonstrate that responsive parenting, characterized by sensitive, timely, and developmentally appropriate caregiving, is consistently associated with improved feeding practices, enhanced dietary adequacy, and superior indicators of child growth. Evidence-based parenting interventions that incorporate caregiver coaching, home-based monitoring, and parental empowerment are more effective than standard counseling approaches. Conclusion Furthermore, responsive caregiving contributed to better appetite regulation, reduced feeding difficulties, and increased psychosocial stimulation, collectively supporting catch-up growth in children affected by stunting. These findings underscore the need to integrate responsive parenting strategies into nutrition and stunting-reduction programs to enhance children's nutritional recovery and developmental outcomes